The effect of intake of water on the final values of body composition parameters in active athletes using two different bioimpedance analyzers - Petr Kutáč (Palacký University Olomouc, 2014)
Background:The method of bioelectrical impedance (BIA) is frequently used to estimate body composition in sports. The total body water (TBW) is the basic variable that BIA measures. That implies the degree of sensitivity of BIA to the hydration of the organism, which is also demonstrated by the principles of measurement that primarily relate to the hydration of the organism. It is difficult to provide standard hydration of the organism of subjects prior to measurements when taking the measurements in the field. Objective:The objective of the study is to assess the changes in the final values of the selected body composition parameters in soccer players caused by intake of water, using two devices commonly used in the field. Methods:The research was performed in a group of 33 soccer players (mean age 20.30 ± 1.18 years). The measurements were taken using Tanita BC 418 MA (frequency 50 kHz) and Nutriguard-M (frequency 100 kHz). To evaluate the effect of water intake, we took two measurements before and after the intake of 500 ml of water. The parameters measured by Tanita BC 418 MA were body weight (BW), total body water (TBW), body fat (BF), fat free mass (FFM). Nutriguard-M was used to measure total body water (TBW), intra and extracellular water (ICW and ECW), body fat (BF), fat free mass (FFM), intra and extracellular mass (BCM and ECM). The differences in the means (M1 and M2) of the monitored parameters were evaluated using the Paired Samples t-test. In statistically significant differences in the mean, the practical significance was also verified using the effect of size (Cohen's d). Results:The Tanita device showed statistically significant differences after the intake of 500 ml in parameters BW (+0.42 kg), BF (+0.39 kg, +0.53%) and TBW (-0.38%). As for the Nutriguard device, statistically significant differences were found in parameters TBW (+0.77 kg), ICW (+0.83 kg), FFM (+1.05 kg), BCM (+0.79 kg) and ECM/BCM (-0.01). Conclusion:The water intake had no effect on the final value of the body composition parameters, which was confirmed by the low effect of size values (d = 0.06-0.47) of parameters where statistically significant differences were found. Also, the water intake had no effect on the accuracy of measurement of both devices. The measurements of the standard error of measurements values before and after the water intake did not differ.